(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Dentistry’s field of oral medicine is undergoing ongoing change. Oral medicine has grown in both scope and complexity over the last few years. Oral medicine deals with the diagnosis and treatment of complicated medical and diagnostic conditions that affect the mouth and jaws. The diagnostic field of oral medicine has made significant strides in the last ten years, moving from the lab to dentist offices and hospitals. It’s crucial that these developments don’t just benefit the industry’s experts. To deliver a high level of treatment, every general dentist should be knowledgeable about contemporary developments in diagnostic oral medicine. This essay explores how recent developments in oral medical technology have affected clinical dental practise.